Escuela de niños grandes - Rice, Dona. (Huntington Beach, CA : Teacher Created Materials, 2012)
A young girl imagines all the interesting things that the big children do when they go to primary school.
Keywords: Elementary schools -- Fiction; Schools -- Fiction; Stories in rhyme; Spanish language materials; Elementary schools -- Fiction; Spanish language -- Reading materials; School stories; Stories in rhyme